Effect of apparent temperature on hospitalization from a spectrum of cardiovascular diseases in rural residents in Fujian, China. (15th June 2022) - Zhan, Zhi-Ying; Zhong, Xue; Yang, Jun; Ding, Zan; Xie, Xiao-Xu; Zheng, Zhen-Quan; Hu, Zhi-Jian
Abstract: Cardiovascular disease (CVD) is a leading threat to global public health. Although associations between temperature and CVD hospitalization have been suggested for developed countries, limited evidence is available for developing countries or rural residents. Moreover, the effect of apparent temperature (AT) on the spectrum of cause-specific CVDs remains unknown. Based on 2, 024, 147 CVD hospitalizations for rural residents from eight regions in Fujian Province, China, during 2010–2016, a quasi-Poisson regression with distributed lag non-linear model was fitted to estimate the AT effect on daily CVD hospitalization for each region, and then pooled in a meta-regression that included regional indicators related to rural residents. Stratified analyses were performed according to the cause of hospitalization, sex and age groups. Finally, we calculated the fraction of CVD hospitalizations attributable to AT, as a reﬂection of the burden associated with AT. The heat effect appeared at lag 0–1 days, with 19% (95% CI, 11–26%) increased risk of CVD hospitalization, which was worse for ischemic heart disease, heart failure, arrhythmias and ischemic stroke. The decreased AT was associated with increase of hemorrhagic stroke at lag 0–28 days. People aged 65 and above suffered more from the heat effect on cardiovascular and cerebrovascular diseases. Regions with a lower gross value of agricultural production, rural residents' per capita net income, number of air conditioners and water heaters were more susceptible. A large number of hospitalizations were attributable to heat for most subcategories. High AT level increased CVD hospitalization, and the subcategories had different susceptibilities. The effects were modified by individual and regional characteristics. These findings have important implications for the development of targeted interventions and for hospital service planning. Graphical abstract: Image 1 Highlights: Apparent temperature affected hospitalization of cardiovascular disease (CVD). Cold and heat elevated rural residents' CVD morbidity, and varied across subtypes. The elderly were significantly vulnerable to heat effect. Regions with fewer air conditioners and income were more vulnerable. A 13.58% of CVD attributed to apparent temperature, mostly during hot days.